An algorithm for Bragg coherent x-ray diffractive imaging of highly strained nanocrystals. (20th January 2020) - Wang, Ziyi; Gorobtsov, Oleg; Singer, Andrej
Abstract: By using phase retrieval, Bragg coherent diffractive imaging (BCDI) allows tracking of three-dimensional displacement fields inside individual nanocrystals. Nevertheless, during structural phase transformations, significant strains (1% and higher) are common, and BCDI fails due to the Bragg peak distortions. Here we present and advanced BCDI algorithm enabling imaging three-dimensional strain fields in highly strained crystals with separated structural phases. We test the algorithm on particles simulated to undergo a structural phase transformation. While the conventional algorithms fail in unambiguously reconstructing the phase morphology, our algorithm correctly retrieves the morphology of coexistent phases with a strain difference of 1%. The key novelty is the simultaneous reconstruction of multiple scans of the same nanoparticle at snapshots through the phase transformations. The algorithm enables visualizing phase transformations in nanoparticles of lithium-ion, sodium-ion nanoparticles, and other nanoparticulate materials in working conditions (operando).